Afghanistan Civil War In “Kite Runner” Novel By Khaled Husseini; Historical Approacha - Ardiansyah Ardiansyah (Cordova Journal : languages and culture studies, 2020)
This journal point on the analysis of history in “Kite Runner” novel by Khaled Hosseini in 2003. Many countries ever happened civil war, then the author pour it into literary work, it likes Afghanistan civil war in this novel. The story in this novel told about the beauty of Kabul was replaced by disturbance of the conflict that destroyed Afghanistan. Furthermore, the object of the research is history of Afghanistan civil war in “Kita Runner” novel by Hosseini in 2003 viewed from H. A. Taine phrase. As basic concept and framework thinking, the researcher used elements of race, milieu and moment from historical approach purposed by Taine in Guerin et al (2005). Qualitative descriptive method used as method presenting result, also used primary and secondary data as method to collect data. The researcher found that Afghanistan civil war in this novel is real history occurred in Afghanistan from 1978 until present. From the analysis, it can be concluded the novel of “Kita Runner” by Khaled Hosseini in 2003 is compatible to analyze by used historical approach.